2013
DOI: 10.1002/jsfa.6497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of red ginseng marc and α-tocopherol on the growth performance and meat quality of broiler chicken

Abstract: Supplementation of poultry diets with 3% red ginseng marc markedly reduced mortality and serum cholesterol levels and remarkably improved meat quality in broilers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
(50 reference statements)
4
23
0
2
Order By: Relevance
“…Previous studies have shown that the presence of natural antioxidants could retard the formation of metmyoglobin and have highly suppressive effects and decrease L* or increase a* values (Fernandez-Lopez et al, 2005;Velasco and Williams, 2011). In contrast, Kim et al (2014) suggested that the color of the thigh muscle was not affected by supplementation of broiler diets with increased levels of red ginseng marc.…”
Section: Ph and Meat Colormentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies have shown that the presence of natural antioxidants could retard the formation of metmyoglobin and have highly suppressive effects and decrease L* or increase a* values (Fernandez-Lopez et al, 2005;Velasco and Williams, 2011). In contrast, Kim et al (2014) suggested that the color of the thigh muscle was not affected by supplementation of broiler diets with increased levels of red ginseng marc.…”
Section: Ph and Meat Colormentioning
confidence: 97%
“…This result implies that the combination of fermented red ginseng marc and red-koji or red 1 C=Control (no treatment); T1=2% red ginseng marc; T2=1% fermented red ginseng marc with red-koji; T3=2% liquid red ginseng ginseng marc may be important for improving antioxidant properties during storage. In other words, an increase in DPPH radical-scavenging activity has a positive impact on meat quality, possibly because of the saponins present in red ginseng marc and the ability to serve as efficient free-radical scavengers (Kim et al, 2014). Kim et al (2014) showed that DPPH radical-scavenging activity in thigh meat increased significantly with increasing levels of red ginseng marc.…”
Section: Dpph Radical-scavenging Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Red ginseng marc is a water-insoluble byproduct remaining after the red ginseng extraction process. The positive effects of red ginseng marc have gained much attention, as shown in two studies that examined the effects of dietary red ginseng marc on the growth and meat quality of pigs and broilers (Ao et al, 2011a;Kim et al, 2014). In Korea, red ginseng marc is unfortunately discarded as a waste material, even though it has many suggested positive uses .…”
Section: Growth Performance and Fatty Acid Profiles Of Broilers Givenmentioning
confidence: 99%